Kemudahan dan Efisiensi M-Banking Sebagai Solusi Praktis di Era Digital - Ananda, Annisa Septri; Fasa, Muhammad Iqbal (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
The presence of mobile banking can have a positive impact because the main purpose of Mobile Banking is to facilitate customers in conducting every transaction they wish to make. The aim of this research is to determine the ease and efficiency of customers' interest in transacting using mobile banking in the digital era. This research is a qualitative study that collects secondary data through a literature review. The existence of mobile banking technology certainly aids the efficiency of its users, as it makes things easier for them. Mobile banking technology can be used at any time with peace of mind, without worrying about the privacy of personal data, thanks to a good service system that also maintains its image.